Comparative Transcriptome Analysis of Streptomyces nodosus Mutant With a High-Yield Amphotericin B - Huang, Kai; Zhang, Bo; Chen, Yu; Liu, Zhi-Qiang; Zheng, Yu-Guo (Frontiers in Bioengineering and Biotechnology, 2021)
Antibiotics play an important role in human health. Most antibiotics are derived from microbial secondary metabolites. Amphotericin is a polyene macrolide antibiotic synthesized by Streptomyces nodosus. S. nodosus ZJB2016050 with high-yield amphotericin B (AmB) was obtained by traditional mutagenesis using S. nodosus ATCC14899 as original strain. The differences in the characterization of the two strains were found in color, mycelium morphology and AmB yield. Subsequent comparative transcriptome explained the yield differences between the two strains. Pathways including carbohydrate metabolic pathway and secondary product synthesis pathway were targeted. The up-regulation of glucokinase, phosphoglycerate mutase and pyruvate dehydrogenase accelerate the consumption of glucose and have great effects on the accumulation of precursors. One of the competitive secondary metabolites of polyketone synthetase (PKS) II type sapromomycin analogue synthesis gene cluster was down-regulated, which compete for malonyl-CoA. Five PKS modules (except for the first module amphA) of amphotericin synthetic gene cluster in the high-yielding strain were downregulated, which resulted in the total amphotericin A (AmA) and AmB of S. nodosus ZJB2016050 being less than that of the wild-type S. nodosus ATCC14899. Combined with genes differential expression in pentose phosphate pathway and reaction mechanism of ER5 domain, the reason that S. nodosus ZJB2016050 preferred to synthesize AmB was probably related to intracellular reduction.